Follicular helper T cell signature of replicative exhaustion, apoptosis, and senescence in common variable immunodeficiency. Issue 7 (29th May 2022) - Milardi, Giulia; Di Lorenzo, Biagio; Gerosa, Jolanda; Barzaghi, Federica; Di Matteo, Gigliola; Omrani, Maryam; Jofra, Tatiana; Merelli, Ivan; Barcella, Matteo; Filippini, Matteo; Conti, Anastasia; Ferrua, Francesca; et al.
Abstract: Common variable immunodeficiency (CVID) is the most frequent primary antibody deficiency whereby follicular helper T (Tfh) cells fail to establish productive responses with B cells in germinal centers. Here, we analyzed the frequency, phenotype, transcriptome, and function of circulating Tfh (cTfh) cells in CVID patients displaying autoimmunity as an additional phenotype. A group of patients showed a high frequency of cTfh1 cells and a prominent expression of PD‐1 and ICOS as well as a cTfh mRNA signature consistent with highly activated, but exhausted, senescent, and apoptotic cells. Plasmatic CXCL13 levels were elevated in this group and positively correlated with cTfh1 cell frequency and PD‐1 levels. Monoallelic variants in RTEL1, a telomere length‐ and DNA repair‐related gene, were identified in four patients belonging to this group. Their blood lymphocytes showed shortened telomeres, while their cTfh were more prone to apoptosis. These data point toward a novel pathogenetic mechanism in CVID, whereby alterations in DNA repair and telomere elongation might predispose to antibody deficiency. A Th1, highly activated but exhausted and apoptotic cTfh phenotype was associated with this form of CVID. Abstract : Patients with common variable immunodeficiency with no previous genetic diagnosis presenting additionally one autoimmune symptom were compared to healthy subjects. Circulating follicular helper T (Tfh) cells were analyzed for their phenotype and function by flow cytometry, while their transcriptome was determined with RNA seq. Genetic analysis was performed by WES and validated by Sanger Sequencing. An integrated pipeline led to the identification of a cluster of patients characterized by a Th1 Tfh signature, elevated plasma CXCL13 levels, shortened telomeres, and enlarged lymph nodes and spleen. Rare monoallelic mutations in RTEL1 were identified as a possible common denominator. Further analyses revealed Tfh replicative exhaustion as a possible underlying mechanism.